TEATER MUSIKAL ANAK "PEMETIK SENYUMAN" OLEH NUART SCHOOL OF MUSICAL THEATRE (Analisis Proses Penggarapan Musik) - Nirvana Vania, - (2020)
Musical theatre is a form of theatrical performance that combines song, oral dialogue, acting, and dance. The story and emotional content of the music - humor, sadness, love, anger - is communicated through words, music, movement, and the technical aspects of entertainment as one whole. Departing from a poem transformed into a performance requires the high creative ability of a composer in the work in terms of the scope of the performing arts and music also has a crucial role as a trigger or mood-grinder. The study was titled "Teater Musikal Anak "Pemetik Senyuman" oleh Nuart School of Musical Theater (Analisis Proses Penggarapan Musik)". The problems and objectives of this study are to describe and analyze the process of interpretation of music, the process of music, and the presentation of performances in children's musical theater "Pemetik Senyuman". The method used in this study is a descriptive method of analysis with a qualitative approach. Data collection conducted by researchers through logbooks provided by mentors, interviews, documentation, and library studies. The results of this study explain that the co-ordination of directors and their ranks is transformed into an ensemble work based on knowledge and skill, the results of which can realize the Nuart School of Musical Theatre program in accordance with the expectations for the early stages of the introduction process about musical theatre in children. Keywords: Analysis, Musical Theatre, Interpretation, Process, Music Presentation.